Commemoration in crisis: A discursive analysis of who 'we' and 'they' have been or become in ceremonial political speeches before and during the Greek financial downturn. (17th February 2018) - Gkinopoulos, Theofilos; Hegarty, Peter
Abstract : This study analyses the discourse of statements of the leaders of two Greek political parties commemorating the restoration of Greek democracy on 24 July 1974; the ruling party New Democracy and the opposition, Coalition of the Radical Left. We focus on how these leaders act as entrepreneurs of their identities by constructing their ingroups in broad or narrow terms and their outgroups in vague or specific terms. These constructions were ventured during a period of relative political stability (2008) and instability (2012), and we focus on how ingroup prototypes and group boundaries are narrated across Greece's past, present and future in ambiguous or concrete terms. The study aligns the social identity approach to political leadership with studies on political discourse and 'the rhetoric of we'. We view commemorative statements as historical charters and respond to calls for discourse analysis to take greater account of historical context. The findings suggest concrete hypotheses about how leaders with different amounts of political support might define, as identity entrepreneurs, who 'we' are, and who 'we' are not in democratic contexts marked by stability or crisis.